Nanostructured TTT(TCNQ)2 organic crystals as promising thermoelectric n-type materials: 3D modeling - Sanduleac, Ionel; Casian, Anatolie (Springer, 2016)
Thermoelectric properties of quasi-one-dimensional TTT(TCNQ)2 organic crystals are investigated in order to appreciate the prospect of using this compound as n–type thermoelectric material. A more complete three-dimensional (3D) physical model is elaborated. It takes into account two the most important interactions of conduction electrons with longitudinal acoustic phonons, the electrons’ scattering on neighbor molecular chains, as well as the scattering by impurities and defects. The electrical conductivity, thermopower, the power factor, electronic thermal conductivity and the thermoelectric figure of merit in the direction along conductive molecular chains are calculated numerically for different degrees of crystal purity. It is shown that in stoichiometric compounds the thermoelectric figure of merit ZT remains small even after the increase of crystal perfection degree. The thermoelectric properties may be significantly enhanced by simultaneous increase of crystal perfection and of electron concentration. The latter can be achieved by additional doping with donors. For less pure crystals, the interaction with impurities predominates over the weak interchain interaction and the simpler one-dimensional (1D) physical model is applicable. When the impurity scattering is reduced, the interchain interaction begins to limit the carrier mobility and the application of the 3D physical model is required. The optimal parameters permitting to predict ZT~ 1 are determined.